Properties of simulated galaxies and supermassive black holes in cosmic voids - Habouzit, Mélanie; Pisani, Alice; Goulding, Andy (Monthly notices of the Royal Astronomical Society, 2020)
ABSTRACT. Cosmic voids, the underdense regions of the cosmic web, are widely used to constrain cosmology. Voids contain few, isolated galaxies, presumably expe
Gesehen am 15.04.2020